2020
DOI: 10.5334/gh.529
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Rheumatic Heart Disease Echocardiographic Screening in Brazil: Data from the PROVAR+ Study: Cost-effectiveness of RHD screening in Brazil

Abstract: Introduction: In recent years, new technologies-noticeably ultra-portable echocardiographic machines-have emerged, allowing for Rheumatic Heart Disease (RHD) early diagnosis. We aimed to perform a cost-utility analysis to assess the cost-effectiveness of RHD screening with handheld devices in the Brazilian context. Methods: A Markov model was created to assess the cost-effectiveness of one-time screening for RHD in a hypothetical cohort of 11-year-old socioeconomically disadvantaged children, comparing the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
(38 reference statements)
0
15
0
2
Order By: Relevance
“…Uma estratégia baseada em divisão de tarefas, com aquisição de imagem por não médicos, utilizando dispositivos portáteis, e telemedicina para interpretação remota por especialistas, resultou em uma razão de custo-efetividade incremental de $10.148,38 por DALY evitado, abaixo do limiar estimado de 3 vezes o produto interno bruto per capita, sugerido pela Organização Mundial da Saúde. 212 …”
Section: Utilização E Custo Da Atenção à Saúdeunclassified
“…Uma estratégia baseada em divisão de tarefas, com aquisição de imagem por não médicos, utilizando dispositivos portáteis, e telemedicina para interpretação remota por especialistas, resultou em uma razão de custo-efetividade incremental de $10.148,38 por DALY evitado, abaixo do limiar estimado de 3 vezes o produto interno bruto per capita, sugerido pela Organização Mundial da Saúde. 212 …”
Section: Utilização E Custo Da Atenção à Saúdeunclassified
“…Nevertheless, we have demonstrated that a rapid single-view screening protocol can be performed in just over one-minute with a high degree of accuracy. School-based screening programs appear to be cost effective and reduce the risk of RHD overtime [5,18,19]. As new evidence emerges and technology improves, increased funding for RHD is needed to meaningfully reduce the global burden of disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…The investments required for local surgery capacity were high with limited impact (ICER of USD 23,827 per DALY averted for building a local center) [209]. Several other publications have separately explored optimum cost-effective strategies for primary prevention [210], secondary prevention [211][212][213][214], and a combination of both [214][215][216]. A most recent modeling study for the prevention and management of RHD in the African Union concluded that, "In the short term, costs of secondary prevention and secondary and tertiary care for RHD are lower than for primary prevention, and benefits accrue earlier [217]".…”
Section: Understanding Of Rhd-associated Costs In Endemic Regionsmentioning
confidence: 99%
“…A most recent modeling study for the prevention and management of RHD in the African Union concluded that, "In the short term, costs of secondary prevention and secondary and tertiary care for RHD are lower than for primary prevention, and benefits accrue earlier [217]". Most analyses make use of Markov models, and similar challenges relating to lack of precise transition probabilities on which to base the calculations have been reported [209,212,215].…”
Section: Understanding Of Rhd-associated Costs In Endemic Regionsmentioning
confidence: 99%